Dekonstruksi Pendidikan Islam Sebagai Subsistem Pendidikan Nasional - Suyatno, Suyatno (Jurnal Pendidikan Islam, 2012)
The dualism of the nationally educational system has become the object of debate in various forums and educational seminars. The dualism of the educational system is the continuity of history; both in the history of the Muslims in particular and the history of Indonesian people in general. In addition, the discourse of dualism also gained back the education system due to political turmoil ideology. Whatever the reason, dualism has some nationally negative impact on educational institutions in Indonesia mostly in Islamic educational institutions. Therefore, it was the time that education in Indonesia must be under the policy of the ministry of education to make one-policy of the educational system.